2010
DOI: 10.1155/2010/858606
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Dynamics of Myofibrils

Abstract: We review some of the problems in determining how myofibrils may be assembled and just as importantly how this contractile structure may be renewed by sarcomeric proteins moving between the sarcomere and the cytoplasm. We also address in this personal review the recent evidence that indicates that the assembly and dynamics of myofibrils are conserved whether the cells are analyzed in situ or in tissue culture conditions. We suggest that myofibrillogenesis is a fundamentally conserved process, comparable to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 65 publications
(115 reference statements)
9
140
1
1
Order By: Relevance
“…Thus, the organization of actin filaments in premyofibrils resembles that of stress fibers in non-muscle cells (Sanger et al, 2005, Sanger et al, 2009. Although many sarcomeric proteins are present in premyofibrils, they contain non-muscle myosin II instead of the muscle-specific myosin II isoform (Handel et al, 1991;Sanger et al, 2010). Premyofibrils thus display some similarities to the transverse arcs of nonmuscle cells and might also utilize similar pathways for their assembly (Sanger et al, 2009;Sparrow and Schöck, 2009).…”
Section: Regulation Of Stress Fiber Contractionmentioning
confidence: 99%
“…Thus, the organization of actin filaments in premyofibrils resembles that of stress fibers in non-muscle cells (Sanger et al, 2005, Sanger et al, 2009. Although many sarcomeric proteins are present in premyofibrils, they contain non-muscle myosin II instead of the muscle-specific myosin II isoform (Handel et al, 1991;Sanger et al, 2010). Premyofibrils thus display some similarities to the transverse arcs of nonmuscle cells and might also utilize similar pathways for their assembly (Sanger et al, 2009;Sparrow and Schöck, 2009).…”
Section: Regulation Of Stress Fiber Contractionmentioning
confidence: 99%
“…Myofibril assembly begins at the Z-disk (reviewed in Ehler and Gautel, 2008;Sanger et al, 2010). Here, antiparallel actin filaments are crosslinked and capped at their barbed ends, leading to tetragonal arrays of precisely tailored thickness (Figs 1-3).…”
Section: Z-disk Cytoskeleton: Form Follows Function?mentioning
confidence: 99%
“…There appears to be no change in Z-disk thickness, however. Whether the sprint performance advantage of wild-type ACTN3 carriers is due to subtle differences in molecular mechanical properties or in the interaction with any of the many α-actinin interacting proteins that link to cellular signalling and metabolic pathways (Djinovic-Carugo et al, 2002;Lange et al, 2006;Linke and Kruger, 2010;Sanger et al, 2010) is currently unclear. However, these observations underscore the role of the sarcomeric cytoskeleton as not only a passive scaffold but also a determinant of muscle performance and metabolism (Berman and North, 2010), which has recently been linked to differential transcriptional regulation by calcineurin via calsarcin-2/myozenin-1/FATZ-1 at the α-actinin scaffold (Seto et al, 2013).…”
Section: Z-disk Cytoskeleton: Form Follows Function?mentioning
confidence: 99%
See 1 more Smart Citation
“…The general pattern of differentiation of cultured cardiac muscle cells has been reported elsewhere (DeHaan and Hirakow, 1972;Schultheiss et al, 1990;Ono, 2010;Sanger et al, 2010) and will not be reported here.…”
Section: Resultsmentioning
confidence: 90%